2011
DOI: 10.1007/s11661-011-1001-8
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Nucleation Kinetics of Microporosity Formation in Aluminum Alloy A356

Abstract: Metal cleanliness is one of the most critical parameters affecting microporosity formation in aluminum alloy castings. It is generally acknowledged that oxide inclusions in the melt promote microporosity formation by facilitating pore nucleation. In this study, microporosity formation under different casting conditions, which aimed to manipulate the tendency to form and entrain oxide films in small directionally cast A356 samples was investigated. Castings were prepared with and without the aid of argon gas sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
2
7
0
Order By: Relevance
“…This mechanism is in agreement with the results of Liu et al [54] and provides an explanation on how the number of pores increased with Sr additions [55]. Yao et al [56] had shown that in the presence of Sr, oxidation increased and nucleation of pores decreased.…”
Section: Number Density Measurementssupporting
confidence: 92%
“…This mechanism is in agreement with the results of Liu et al [54] and provides an explanation on how the number of pores increased with Sr additions [55]. Yao et al [56] had shown that in the presence of Sr, oxidation increased and nucleation of pores decreased.…”
Section: Number Density Measurementssupporting
confidence: 92%
“…When the casting temperatures are 670 C, 700 C and 730 C, the hydrogen porosity defect number (N) of the A380 ingots decreases from No EMT casting's 274, 473, and 572 to EMT casting's 193, 204 and 297, while the hydrogen porosity defect distribution density (Nd) decreases from No EMT casting's 7.6, 13.1 and 16.1 cm À2 to EMT casting's 5.5, 5.8 and 8.2 cm À2 . The diameter of the hydrogen porosity defect in No EMT and EMT casting A380 ingots ranges from 50 mm to 500 mm, and the average diameter of the hydrogen porosity defect (d m ) is about 250 mm, which is consistent with references [3,29,37,42]. Fig.…”
Section: Effect Of Emt On Hydrogen Porosity Defectsupporting
confidence: 86%
“…For the heterogeneous nucleation mechanisms of hydrogen pores in aluminum alloys during the solidification process, the conventional theory suggests that oxide inclusions in the melt serve as heterogeneous nucleation sites [29], while new nucleation mechanism based on the entrainment of surface oxide bi-films during the pouring process was proposed by Campbell [30,31], and there is still no final conclusion for the two argumentative mechanisms [42]. As shown in Fig.…”
Section: Effect Of Emt On Hydrogen Porosity Defectmentioning
confidence: 99%
See 1 more Smart Citation
“…41) It is known that the porosity with larger size will have important impact on the fatigue strength and tensile strength. 16,39,40) Figure 7 presents the maximum porosity radius varying with cooling rate at different initial hydrogen concentrations. Note that with the decrease of cooling rate, the final maximum porosity radius increases.…”
Section: Effect Of Initial Hydrogen Concentrationmentioning
confidence: 99%